Berbisnis Online Lewat Padi UMKM Lebih Maju Dan Menguntungkan - Musthafa Kamil (LPPM Universitas Dharma Andalas, 2023)
The presence of the internet has provided a wider new opportunity for doing business, namely through online business. Teachers can also take advantage of this internet presence to increase their income by running a business according to their profession, without having to leave their assignments because they are done from home outside of teaching hours. Online business can be done with or without own website. People can use smartphones, tablets or laptops connected to the internet. Online business activities can be carried out anytime and from anywhere, as long as communication facilities are available. In response to this it is felt important to hold community service which is aimed at the Teachers and Management of the Darul Hikmah Al-Qur'an Education Park (TPQ) located Jl. H. Terin Rt. 006/RW. 003 Pangkalan Jati Baru Cinere Depok, West Java. This community service is in the form of an online business workshop through PaDi UMKM which is more advanced and profitable with participants from teachers and administrators of TPQ Darul Hikmah. It is hoped that there will be an increase in the knowledge of teachers and administrators that can be applied in business life. Some of the committee used zoom and some at TPQ Darul Hikmah. Hopefully the welfare of the teachers and administrators of TPQ Darul Hikmah will increase.